The management of outreach and poverty reduction in microfinance institutions in South Asia - Uddin, Md Nazim; Haque, A K M Ahasanul; Nahar, Lutfun (2024)
A microfinance institution is an organisation that offers financial services to those who are unable to get financial services from traditional banks due to factors such as economic disadvantage, unemployment, or other similar factors. Most microfinance institutions have difficulty balancing servicing many low-income customers and making enough money to be self-sufficient. This study aims to determine the elements that affect the outreach efforts of MFIs in South Asia. In quantitative research, secondary data from sources such as the MIX market and the World Bank are used. In addition, the data was collected from thirty MFIs, and the MFIs included in the sample were chosen according to the percentage of their complete data for each of the five time periods that fell between 2017 and 2021. For the analysis of the panel data, STATA 16.1 was used. According to the conclusions of this analysis, one of the most important contributors to the financial performance of MFIs is their overall size. In addition to this, the expansion of South Asia's GDP has a significant influence on the operational self-sufficiency of MFIs. The study reveals the factors that contribute to the success of MFIs and provides crucial knowledge to people interested in MFIs.